Identification of Antioxidant Activity of Ethanol Extracts from (Hedyotis corymbosa L.) Pearl Grass Leaves Against Oxidative Stress - Faiza, Nurul; Nabila, Salma; Purnamasari, Risa; Agustina, Eva; Nova Lusiana; Hidayati, Irul; Andiara , Funsu (International Conference on Sustainable Health Promotion, 2025)
Oxidative stress is the main causative factor of various degenerative diseases, and the search for natural antioxidant sources becomes important to overcome this problem. This study aims to identify the activity of antioxidant compounds from ethanol extract of pearl grass (Oldenlandia corymbosa) leaves in neutralizing free radicals. The methods used include leaf extraction with 70% ethanol and antioxidant activity testing using UV-Vis spectroscopy at a wavelength of 517 nm. Results showed that the extract with a concentration of 80 ppm produced a maximum inhibition of 51.60%, indicating significant antioxidant potential. Qualitative phytochemical tests identified the presence of phenolic compounds and flavonoids, which act as electron donors in the free radical penetration process. The IC50 value of the ethanol extract obtained was 46 µg/mL, indicating the effectiveness of the extract in inhibiting free radicals. These findings support the potential of pearl grass as a source of natural antioxidants that can be further developed for the prevention and therapy of oxidative stress-related degenerative diseases.